Implementation of Diversion System on Juvenile Delinquency to Manifest Restorative Justice at Badan Pemasyarakatan Kelas II (Class II Correctional Institution) in Samarinda - Herliah, Endang (Salasika, 2024)
This study explores the application of the Diversified Penal System for Children (DPS) in overcoming the phenomenon of juvenile delinquency, focusing on the application of Restorative Justice in Badan Pemasyarakatan (BAPAS) Kelas II (Class II Correctional Institution) in Samarinda. This study aims to analyze the role of the Bapas in handling law cases involving children, especially in the context of sexual crimes. The data were gathered through normative legal research and secondary data sources, such as legal documents and interviews with key stakeholders, including the Head of Client Guidance of Bapas Kelas II Wonosari, the Judge of the Bantul District Court, and child investigators at the Samarinda Regional Police. This study examined the challenges faced by the Bapas in handling cases of child offenders and Bapas’ recommendations and suggestions. The findings of this study are hoped to shed light on the role of Bapas in Indonesia's legal framework, particularly the Juvenile Justice System Law of 2012.